MODELING THE INTERDEPENDENCE OF MARKETING AND ACCOUNTING INFORMATION SYSTEMS - Perica Macura; Predrag Gajić (Acta Economica, 2022)
This paper presents a model of interdependence of marketing information system and accounting information system activities, with the aim of harmonizing them while identifying activities on the basis of which the goals of information support for the execution of managerial tasks are completed. The lack of effort to create such models in the past can be explained by the tendency to present individual information systems as integral and sufficient for management needs. However, the growing management informational dependence of a company implies the need for more efficient ways to create and deliver relevant information and reports. The proposed model is based on a general management concept according to which, under the contemporary business conditions, three general groups of activities are performed: research and monitoring of market requirements, creation of value for customers based on previously identified needs and customer relationship management, and customer lifecycle management. On the basis of such grouped management tasks, marketing and accounting activities and their mutual conditionality were identified and unified though the proposed model.